2009
DOI: 10.1097/med.0b013e3283295297
|View full text |Cite
|
Sign up to set email alerts
|

Statin and ezetimibe combination therapy in cardiovascular disease

Abstract: The combination of ezetimibe, a cholesterol absorption inhibitor, and statins has been shown to be well tolerated and effective in lowering LDL-C and high-sensitivity C-reactive protein to target goals. Whether this greater LDL-C reduction translates into reduced cardiovascular events is the subject of ongoing clinical trials. Until such data is available, ezetimibe seems to be a reasonable choice for a second-line, lipid-lowering agent in patients on a potent statin who are not at their LDL-C goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Traditionally, ezetimibe is administered to patients already receiving statin therapy. 28 The finding that the combined treatment started simultaneously was well tolerated indicates that the administration of both a statin and ezetimibe may be initiated at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, ezetimibe is administered to patients already receiving statin therapy. 28 The finding that the combined treatment started simultaneously was well tolerated indicates that the administration of both a statin and ezetimibe may be initiated at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study was short in duration, did not assess clinical outcomes, and the study population, although exceeding the required sample size, was relatively low. Second, the doses of both simvastatin and ezetimibe, although commonly used in the clinical practice, 28 are not the maximal, ones and therefore, it remains unanswered whether the effects of these agents on cytokine release and plasma hsCRP is stronger when they are given at highest doses. We cannot exclude the fact that for ezetimibe a reduction in cytokine release may reach the level of significance, provided more patients are enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Foley et al [7] demonstrated that 52% of high-risk hyperlipidemic patients did not achieve the LDL-C goal with an initial dose of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins), and that 86% of these patients had still not reached the goal after 6 months. Dembowski et al showed that only 18% of these patients achieved the LDL-C treatment goal with statin monotherapy [8]. One reason is that the initiation dose of statins is most effective and doubling the dose achieves only a 6% additional reduction in LDL-C levels [9].…”
Section: European and Other Societies On Cardiovascular Disease Prevementioning
confidence: 99%
“…5 As monotherapy, ezetimibe at 10 mg reduces LDL-C by approximately 17%, but when added to any dose of statin, it reduces LDL-C by an additional 25%. 6 Given the well-established log-linear relationship between LDL-C and relative risk for CHD, these greater degrees of LDL-C reduction can be expected to result in improved clinical outcomes, although this has not yet been proven in the case of ezetimibe. 1,6 Existing data have not established a lower threshold beyond which LDL-C reduction ceases to be beneficial.…”
Section: Article See P 28mentioning
confidence: 99%
“…6 Given the well-established log-linear relationship between LDL-C and relative risk for CHD, these greater degrees of LDL-C reduction can be expected to result in improved clinical outcomes, although this has not yet been proven in the case of ezetimibe. 1,6 Existing data have not established a lower threshold beyond which LDL-C reduction ceases to be beneficial. In secondary prevention, the Treating to New Targets (TNT) study in patients with CHD demonstrated that intensive statin therapy to a mean LDL-C of 77 mg/dL, as compared with a mean LDL-C of 101 mg/dL in the standard treatment group, confers a 22% relative reduction in the risk of a first major cardiovascular event, with no clinically significant increase in adverse event rates.…”
Section: Article See P 28mentioning
confidence: 99%